2020
DOI: 10.21203/rs.3.rs-86952/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA Methylation in OPG/RANK/RANKL Pathway is Associated with Steroid-induced Osteonecrosis of the Femoral Head

Abstract: Background: The dysregulation of OPG/RANK/RANKL signaling pathway is a key step in the occurrence of steroid-induced osteonecrosis of the femoral head (ONFH). This study aims to understand the degree of methylation of OPG, RANK and RANKL genes in steroid-related ONFH.Methods: A case-control study was designed, including 50 patients and 50 controls. The Agena MassARRAY platform is used to detect the methylation status of OPG, RANK and RANKL genes in the blood of subjects. The relationship between the methylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It has been reported that the dysregulation of the OPG/ RANK/RANKL signaling pathway is a key step in the occurrence of steroid-induced ONFH [28]. miR-34a has been found to alleviate steroid-induced ONFH through regulating the OPG/RANK/RANKL signaling pathway [29].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the dysregulation of the OPG/ RANK/RANKL signaling pathway is a key step in the occurrence of steroid-induced ONFH [28]. miR-34a has been found to alleviate steroid-induced ONFH through regulating the OPG/RANK/RANKL signaling pathway [29].…”
Section: Discussionmentioning
confidence: 99%